Pengaruh Penerapan Asuhan Keperawatan Berfokus Pada Kebutuhan Spiritual Terhadap Kepuasan Pasien - Okiyana, Soviyani; Fadilah, Harif; Widiastuti, Eni; Hadi, Muhammad (Universitas Malahayati, 2025)
ABSTRACT Spiritual needs are indispensable for patients with acute, chronic or terminal illnesses as they are an important aspect of the healing process. The implementation of holistic and comprehensive nursing care is expected to provide patient satisfaction which has a positive impact on the quality of nursing services. This study aims to determine the effect of the implementation spiritual needs nursing care on patient satisfaction in the Hemodialysis Unit. This study used the Generalized Linear Model Repeat Measure (GLM-RM) method to analyze the effect of the application of spiritual needs nursing care on patient satisfaction. There is a significant effect on patient satisfaction before and after the application of spiritual nursing care in the intervention group with a p-value = 0.000 (<0.05). Based on the parameter estimates test, the strength of the difference was 42.9%, meaning that there was an effect on patient satisfaction from the first measurement between the control group and the intervention group. Conclusion: The implementation of nursing care focusing on spiritual needs has an influence on patient satisfaction in the Hemodialysis Unit. It is expected that every health service can implement spiritual nursing care standards in an effort to improve patient satisfaction. Keywords: Spiritual Needs, Nursing Care Implementation, Patient Satisfaction ABSTRAK Kebutuhan spiritual hal yang sangat diperlukan pasien yang mengidap penyakit akut, kronis ataupun terminal karena termasuk aspek penting dalam proses penyembuhan. Penerapan asuhan keperawatan secara holistik dan komprehensif diharapkan dapat memberikan kepuasan pasien yang berdampak positif terhadap kualitas layanan keperawatan. Penelitian ini bertujuan untuk mengetahui pengaruh penerapan asuhan keperawatan kebutuhan spiritual terhadap kepuasan pasien di unit Hemodialisis. Penelitian ini menggunakan metode Generalized Linear Model Repeat Measure (GLM-RM) yaitu untuk menganalisia pengaruh penerapan asuhan keperawatan kebutuhan spiritual terhadap kepuasan pasien.Terdapat pengaruh yang signifikan terhadap kepuasan pasien sebelum dan sesudah dilakukan penerapan asuhan keperawatan spiritual pada kelompok intervensi dengan nilai p-value = 0.000 (< 0.05). Berdasarkan uji parameter estimates, didapatkan kekuatan perbedaan 42,9% artinya terdapat pengaruh kepuasan pasien dari pengukuran pertama antar kelompok kontrol dan kelompok intervensi. Penerapan asuhan keperawatan berfokus pada kebutuhan spiritual mempunyai pengaruh terhadap kepuasan pasien di Unit Hemodialisis. Diharapkan setiap layanan kesehatan dapat menerapkan standar asuhan keperawatan spiritual dalam upaya meningkatkan kepuasan pasien. Kata Kunci: Kebutuhan Spiritual, Penerapan Asuhan Keperawatan, Kepuasan Pasien.